WAYS OF REVITALIZATION OF DNIPRO RESERVOIRS - Sharyi Г.; Nesterenko С.; Stoiko Н. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2022)
Society and the state face the urgent problem of preserving and restoring the ecological balance in nature, the integrated rational use of artificially created water bodies and territories. These tasks are provided for in the national target program for the development of water management and ecological rehabilitation of the Dnieper River basin for the period until 2021. However, these tasks have not been implemented. The article studies the factors negatively effecting the environmental situation around the Kremenchuh Reservoir. It is noted that reservoirs cannot exist in the conditions of self-regulation, because they are man-made structures and must be constantly maintained by people in to keep environmentally sustainable conditions. It has been analysed that over the years the conditions of artificial reservoirs have been deteriorated, so it is necessary to comprehensively investigate the factors that negatively affect the flora and fauna of reservoirs. Ways of ecological renewal of the Dnieper basin, in particular of the Kremenchuh reservoir are offered. The experience of revitalization of reservoirs and coastal areas was studied, in particular, as regards to the integrated coastal zone management. The authors have developed and proposed to build alluvial and bulk peninsulas and islands, canals, which will deepen the bottom of the Kremenchuh reservoir, significantly improve the ecological conditions of waters and return to economic use thousands of hectares of reclaimed land. At the state level, it is necessary to develop the Program for Development of the Dnipro Basin until 2050, which includes the issue of reservoir reconstruction. The authors have considered some issues that must be submitted in this program. This will ensure comprehensive management of reservoirs and coastal areas of the Dnipro River. These proposals will create conditions for reconstruction of the territory in order to reduce the area of shallow water, in order to return flooded areas to lands of housing and public buildings, recreation, forestry, transport, energy, industry, agricultural and environmental protection.